Comprensión de la Violencia Simbolica en las Mujeres Vendedoras de Corabastos, Bogotá Colombia. - Gutiérrez Gómez, Daniela (Universidad Antonio Nariño, 2024)
Symbolic violence against women has been so widely naturalized that it makes part of the daily life of the society we live in, due to since childhood, girls have to live situations in which the stereotypes and the traditional roles of gender where women are considered inferior, vulnerable, weak, etc.